Growth Responses of Superior Varieties of Rice in South Coast of Kebumen Regency - Barokah, Umi; Mulyani, Endang; Nugroho, Rahmat Joko; Sitaresmi, Trias (Akta Agrosia, 2025)
The rice plant (Oryza sativa L.) is a staple food source for most people in Indonesia, including those in Kebumen Regency; hence, any decline in rice productivity will impact national food security. A research was carried out to evaluate the growth responses of nine rice varieties under marginal coastal lands in Kebumen Regency. The varieties tested were Inpari 34 Salin Agritan, Inpari 35 Salin Agritan, Inpari Unsoed 79 Agritan, Inpari 47 WBC, IPB 12S, IPB13S, TP-Padi 1, TP-Padi 2, Ciherang, Cilamaya Muncul. Each variety was planted using a square planting system at a distance of 25cm × 25cm, with a plot size of 4m × 5m. Plant growth variables were plant height, number of tillers, root length, root dry weight, shoot dry weight, root/shoot ratio, 50% flowering age and plant lifespan. Paddy varieties grown in South Kebumen coastal area significantly showed different response in plant height, number of tillers, shoot dry weight, 50% flowering age, and plant lifespan. The varieties of IPB 12S, Inpari 47 WBC, and Inpari 34 Salin Agritan have higher growth and flowering performance in coastal  area that might  be have potential to the tolerance to salinity and drought stresses. Keywords: coastal marginal land, drought rice, salinity